Ensuring Development of the Production Potential in Terms of Implementation of Strategic Initiatives of the Railway Transport - Ovchynnikova, Viktoria; Tolstova, Anna; Obruch, Hanna; Ostroverkh, Hanna (International Journal of Engineering and Technology, 2018)
The article determines importance of forming production strategy for railway transport that takes place under the influence of internal and external factors. It has been established that the most significant influence is caused by internal factors, which are caused, first of all, by the specific features of the main activity of the railway transport, transformational conditions of operation, in particular processes of reforming in the railway industry, and existing state of the production potential. It has been determined that formation of the production strategy of the railway transport is to ensure effective use and development of its own production potential.Based on the use of a combined approach that stipulates combination of resource, process and reserve components of the production potential, and states the goals and results of operation, the authors provide their understanding of the essence of the production potential of railway transport as ability and capabilities of the available resources and business processes to ensure the main business activities of the railway transport companies to achieve their planned results and established goals in terms of operation of the railway industry.Â